BIOART ‒ A NEW CHALLENGE IN CONTEMPORARY ART - PAPUC, Ionel (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
Bioart ‒ a New Challenge in Contemporary Art. Lately, in contemporary art, one can find, more and more often, live animals with the status of artwork. Although animal rights activists consider this a flagrant violation of their most elementary rights, contemporary artists with a wide range of motivation often incorporate the live animal into their work and give it the title of artistic work. Another challenge in contemporary art is biotech art that provides the public with another field of representation that has as main themes its living tissues, cells and nucleus, DNA, bacteria, grafts, patches of tattooed skin, guinea pigs, phosphorescent rabbits, and a wide floral palette. To this trend, several art galleries rallied, that consider the living animal and certain aspects of biotechnological research, artwork, and their exposure as being a natural thing. Moreover, in recent decades, to this new current of bioart, groups of specialists from different fields also joined: biologists, psychologists, anthropologists, sociologists, historians, jurists, philosophers, and heterogeneous groups of art lovers. The questions addressed to all those who accept and consider this original work of art are the following: Why is the live animal in an exhibition, more aesthetically valuable than when it lives in its natural life or in a zoo, and why is the representation of DNA more relevant in the art gallery than in the laboratory?. Lastly, has BioArt any transformative capabilities on the general public?